Investing the effect of learning organization, organizational culture, company reputation on organizational performance - Rays, Muh Rays; Titik, Titik Aryati; Yvonne, Yvonne Augustine (Technium Social Sciences Journal, 2022)
The purpose of this study was to examine the effect of organizational learning, understanding of organizational culture, company reputation on organizational performance and this study used the theory of resources-based view and contingency theory. The data used is primary data. Data were collected using the Google Form survey method to 523 medium and large-scale manufacturing industry companies in Indonesia. While the questionnaires analyzed were 471 medium and large scale manufacturing industrial companies in Indonesia. Test the data analysis software using SEM PLS. The results showed that the learning organization had no effect on organizational performance. Organizational culture, company reputation have a significant positive effect on organizational performance. Keywords: learning organization, organizational culture, company reputation, and performance organization.